Insulin-induced copeptin response in children and adolescents to diagnose arginine vasopressin deficiency - Gippert, Sebastian; Brune, Maik; Choukair, Daniela; Bettendorf, Markus (Hormone research in paediatrics, 2024)
Abstract: Introduction: The diagnosis of arginine vasopressin deficiency (AVD, formerly central diabetes insipidus) remains a challenge. In recent years, stimulated copeptin has emerged as a promising tool to diagnose AVD. Methods: In this single centre retrospective study, we identified paediatric patients with suspected pituitary insufficiency who underwent standard insulin tolerance testing (ITT) previously. Patients with AVD and non-matched controls without polyuria-polydipsia syndrome were identified. Diagnosis of AVD was confirmed retrospectively using comprehensive clinical and diagnostic characteristics. Serum copeptin concentrations were measured using a commercially available automated immunofluorescence assay (B.R.A.H.M.S Copeptin-proAVP KRYPTOR®) in −20°C stored samples collected before and 30, 45, and 60 min after insulin injection. Cut-off analyses were performed using ROC curves. Results: Twenty-five patients with AVD and 43 non-matched controls were available for analysis. Median basal copeptin concentrations of 1.51 pmol/L (IQR: 0.91-1.95; serum osmolarity: 288.5 mmol/L, IQR: 282.3-293.5) increased at a median of 30 min to a maximum of 1.95 pmol/L (IQR: 1.31-2.39) in AVD patients (p = 0.113) and from 4.41 pmol/L (IQR: 3.36-6.68; serum osmolarity: 281.0 mmol/L, IQR: 274.0-286.0, p < 0.001) to a maximum of 8.39 pmol/L (IQR: 4.95-19.72, p < 0.001) in controls. ROC analysis resulted in a cut-off of 3.0 pmol/L for maximum copeptin (91.7% sensitivity, 94.1% specificity) for the diagnosis of AVD. Conclusion: Our results suggest that insulin-stimulated serum copeptin concentrations are a sensitive and specific diagnostic tool for AVD in paediatric patients, which allows us to test multiple pituitary hormone axes simultaneously in a single test.
Gesehen am 31.03.2025